The effect of non-antihypertensive doses of angiotensin converting enzyme inhibitor on myocardial necrosis and hypertrophy in young rats with renovascular hypertension - Matsubara, B. B. [UNESP]; Matsubara, L. S.; Franco, M.; Padovani, J. C.; Janicki, J. S. (International Journal Of Experimental Pathology, 1999)
In renovascular hypertensive rats, low doses of angiotensin converting enzyme (ACE) inhibitors have been found to prevent myocardial hypertrophy independent of blood pressure level. This finding would suggest humoral rather than mechanical control of myocyte growth. The aim of this study was to examine the effect of nonantihypertensive doses of ACE inhibitor on myocardial hypertrophy and necrosis in hypertensive rats. Renovascular hypertension (RHT) was induced in four-week-old Wistar rats. Twenty-eight animals were treated for four weeks with three doses of ramipril (0.01, 0.1 or 1. 0 mg/kg/day, which are unable to lower blood pressure. Fourteen animals were not treated (RHT group). A sham operated, age/sex-matched group was used as control (n = 10). Myocardial histology was analysed in 3 microm thick sections of the ventricle stained with either haematoxylin-eosin, reticulin silver stain or Masson's trichrome. There was a significant correlation between systolic blood pressure and left ventricular to body weight ratio in both sets of animals: untreated plus controls and ramipril-treated rats. ACE inhibition prevented myocyte and perivascular necrosis and fibrosis in a dose-dependent manner. We conclude that myocardial hypertrophy in rats with renovascular hypertension is directly related to arterial pressure, and that this relationship is not affected by nonantihypertensive doses of ACE inhibitor. Myocardial necrosis/fibrosis and coronary artery damage induced by angiotensin II are prevented by ACE inhibitor in a dose-dependent manner, despite the presence of arterial hypertension.